THE COLLABORATIVE STRATEGIC READING (CSR) THROUGH STUDENTS’ READING COMPREHENSION - Muziatun Muziatun; Maryam Katili (Universitas Kuningan, 2020)
This research aim to find out to find out (1) Whether the implementation of Collaborative Strategic Reading (CSR) increase the students’ achievement in reading comprehension at the students of MA Al-Huda Gorontalo. (2) Which aspects of reading get the highest increase in the implementation of Collaborative Strategic Reading (CSR).This research conducts quantitatively which used per-experimental research. The sample of this research is 20 students of the second grade at MA Al-Huda Gorontalo. Reading comprehension test, specifically exposition text is used to collecting the data. The test was an objective test and it used to collecting the data pre-test and the post-test. The result of the pre-test was 261 and the post-test was 341. The hypothesis found that the Tcount ≥ Tlist by the value 9,756 ≥ 2,093. It proves that the Hypothesis (H1) is accepted. Thus, the conclusion is the Collaborative strategic reading (CSR) increases the students’ reading comprehension at MA Al-Huda kota Gorontalo.Keywords: Collaborative Strategic Reading (CSR); reading comprehension.